Ein Beitrag zur Bewertung der Schlachtkörperzusammensetzung an lebenden Jungsauen mit Hilfe der Ultraschall-Messmethode - Uusisalmi, U.; Klautschek, G. (Agricultural and Food Science, 1973)
On account of the high reproductive capacity of pigs the performance testing of sows remains of importance even at a time when there is increasingly widespread utilization of artificial insemination. The implementation of a programme of sow selection, however, depends essentially upon the amount of young sow material which can be brought within the scope of breeding selection. In this connection the ultrasonic method developed for the measurements of the fat provides a relatively inexpensive method, well suited for conditions on the farm, for the assesments of carcass quality in young sows. In the present investigation of performance testing 97 gilts were reared to a live weight of approximately 90 kg. Fat thickness was measured ultrasonically at 14 different anatomical points one day prior to slaughter. One day after slaughter a conventional carcass evaluation of the pigs was performed, as well as a partial dissection of the carcass. A close relationship was obtained between ultrasonic and carcass measurements of fat. Ultrasonic measurements were combined to form indices for obtaining a better picture of the degree of fatness. Points 2, 3, 4, 6, 8, 12, 13 and 14 (in Fig. 1) proved to be good locations for measurement. The following multiple correlations (R) were obtained between the indices and the carcass characteristics; index – skin+fat ratio of carcass 0.77; index – meat+bone ratio of carcass 0.71; index – average backfat 0.80; index – skin+fat of ham 0.66; index – meat+bone of ham 0.45. The correlations indicate that the ultrasonic method can be utilized in the selection of sows.